Biopolymer Lipid Hybrid Microcarrier for Transmembrane Inner Ear Delivery of Dexamethasone - Maximilian George Dindelegan; Violeta Pașcalău; Maria Suciu; Bogdan Neamțu; Maria Perde-Schrepler; Cristina Maria Blebea; Alma Aurelia Maniu; Violeta Necula; Anca Dana Buzoianu; Miuța Filip; Alexandra Csapai; Cătălin Popa (Gels, 2022)
Dexamethasone is one of the most often used corticosteroid drugs for sensorineural hearing loss treatment, and is used either by intratympanic injection or through systemic delivery. In this study, a biopolymer lipid hybrid microcarrier was investigated for enhanced local drug delivery and sustained release at the round window membrane level of the middle ear for the treatment of sensorineural hearing loss (SNHL). Dexamethasone-loaded and dexamethasone-free microparticles were prepared using biopolymers (polysaccharide and protein, pectin and bovine serum albumin, respectively) combined with lipid components (phosphatidylcholine and Dimethyldioctadecylammonium bromide) in order to obtain a biopolymer–liposome hybrid system, with a complex structure combining to enhance performance in terms of physical and chemical stability. The structure of the microparticles was evaluated by FTIR, XRD, thermal analysis, optical microscopy, and scanning electron microscopy (SEM). The encapsulation efficiency determination and the in vitro Dexamethasone release study were performed using UV-Vis spectroscopy. The high value of encapsulation efficiency and the results of the release study indicated six days of sustained release, encouraging us to evaluate the in vitro cytotoxicity of Dexamethasone-loaded microparticles and their influence on the cytotoxicity induced by Cisplatin on auditory HEI-OC1 cells. The results show that the new particles are able to protect the inner ear sensory cells.